Perfil nutricional e uso de recursos ergogênicos em trabalhadores de academias da cidade de Pelotas-RS - Teixeira, Gesiane Dias Trindade (2013)
Introduction: The growing number of fitness centers is followed by an increased consumption of ergogenic supplements by clients and professionals who attend these places. The present study aimed to describe the nutritional profile and the use of ergogenic aids in fitness centers workers. Methods: We conducted a population-based cross-sectional study in all gyms of Pelotas, southern Brazil. Was assessed from standardized questionnaire, the consumption of ergogenic supplements (protein, carbohydrate, anticatabolic, multivitamins and hormonal), markers of dietary intake, frequency of fruit and vegetable intake and body mass index (BMI). In addition, we collected sociodemographic and work variables. Results: Mean age of the 497 respondents was 29.7 years (± 8.3), 57.8% were male and most were in the normal BMI range. Almost a quarter of men and less than 10% of women reported consuming at least one type of supplement. As for food intake, we observed a high frequency of consumption of protein-based products, burgers/sausages and soft drinks. The most reported ergogenic was the anticatabolic (75.4% of men and 71.8% women consumed this type of supplement). The higher fruit intake was reported (40.3%) among respondents who consumed only one supplement and vegetable consumption was more common among those consuming two supplements (45.1%). Conclusions: The population assessed, which is often taken as an example by fitness clubs participants, showed a nutritional profile that could be considered inappropriate, where 25% make use of ergogenic aids, showed a high frequency of consumption of protein and soft drinks. In addition, the intake of fruits and vegetables was below the recommendations and inversely proportional to the consumption of supplements